Computed tomography guided needle biopsy: experience from 1,300 procedures - Chojniak, Rubens (2006)
CONTEXT AND OBJECTIVE: Computed tomography CT guided biopsy is widely accepted as effective and safe for diagnosis in many settings. Accuracy depends on target organ and needle type. Cutting needles present advantages over fine needles. This study presents experience from CT guided biopsies performed at an oncology center. DESIGN AND SETTING: Retrospective study at Hospital do Câncer A. C. Camargo, São Paulo. METHODS: 1,300 consecutive CT guided biopysies performed between July 1994 and February 2000 were analyzed. Nodules or masses were suspected as primary malignancy in 845 cases (65%) or metastatic lesion in 455 (35%). 628 lesions were thoracic, 281 abdominal, 208 retroperitoneal, 134 musculoskeletal and 49 head/neck. All biopsies were performed by one radiologist or under his supervision: 765 (59%) with 22-gauge fine-needle/aspiration technique and 535 (41%) with automated 16 or 18-gauge cutting-needle biopsy. RESULTS: Adequate samples were obtained in 70-92% of fine-needle and 93-100% of cuttingy needle biopsies. The specific diagnosis rates were 54-67% for fine-needle and 82-100% for cutting-needle biopsies, according to biopsy site. For any site, sample adequacy and specific diagynosis rate were always better for cutting-needle biopsy. Among 530 lung biopsies, there were 84 pneumothorax (16%) and two hemothorax (0.3%) cases, with thoracic drainage in 24 (4.9%). Among abdominal and retroperitoneal biopsies, there were two cases of major bleeding and one of peritonitis. CONCLUSION: Both types of needle showed satisfactory results, but cutting-needle biopsy should be used when specific diagnosis is desired without greater incidence of complications.